The Impact of Salafism on Socio-Religious and Political Shifts in Kenya - Fatuma Kassim Mwatamu; Stephen Akaranga Ifedha; Abdulkadir A. Hashim (Indonesian Academy of Social and Religious Research (IASRR), 2025)
Global discourse on Salafism is often dominated by narratives of radicalism and extremism, particularly within the framework of security concerns. Such portrayals, however, obscure the diverse expressions of Salafi thought and practice, especially among women. This study examines the socio-religious and political engagement of Salafi Muslim women in Kenya, using the Maahad Girls’ Training Institute (Maahad GTI) as a case study. It investigates how these women navigate religious identity within a patriarchal context, challenge conventional gender norms, and influence both religious and secular spaces through education, community initiatives, and civic participation. Guided by Saba Mahmood’s (2005) concept of pious agency, the research demonstrates how graduates of Maahad GTI employ religious knowledge as a means of empowerment, ethical responsibility, and social transformation. The analysis further highlights the role of digital platforms in amplifying their voices and expanding their influence. Findings reveal a transformative model of Salafism rooted in moral integrity and civic responsibility, offering an alternative to dominant narratives of militancy. By focusing on women’s agency, this paper calls for a nuanced understanding of Salafism in Kenya and underscores the necessity of incorporating female perspectives in the study of Muslim socio-political movements.